1971
DOI: 10.1104/pp.47.5.644
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Amine Oxidase from Epicotyls of Pisum sativum

Abstract: A procedure has been developed for the purification of amine oxidase (E.C. 1.4.3.4) from etiolated pea epicotyls (Pisum sativum cv. Little Marvel). The enzyme is sensitive to copper chelating reagents and carbonyl reagents, but is not inhibited by sulfhydryl reagents. The purified enzyme has a molecular weight of 1.85 X 105, as determined by sedimentation equilibrium centrifugation, and has been shown to be specifically stimulated by phosphate.enzyme. In addition, the enzymes from bovine and porcine plasma hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

1974
1974
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 24 publications
3
19
0
1
Order By: Relevance
“…This would not be the case with AO-I, however. Finally, the substrate specificities of the two enzymes, although similar, are not exactly the same, and the Kmii values determined with several substrates are lower for AO-1 than those reported for the pea enzyme (13).…”
Section: Reduction Of the Product Of Tnh2 Oxidation With Sodiummentioning
confidence: 86%
See 2 more Smart Citations
“…This would not be the case with AO-I, however. Finally, the substrate specificities of the two enzymes, although similar, are not exactly the same, and the Kmii values determined with several substrates are lower for AO-1 than those reported for the pea enzyme (13).…”
Section: Reduction Of the Product Of Tnh2 Oxidation With Sodiummentioning
confidence: 86%
“…Michaelis constants and maximum velocities, relative to that obtained with TNH2, for several substrates are shown in Table III (13) suggested that the lower value reported by Hill and Mann (5) was the result of subunit dissociation during the procedures used for electron microscopy. This would not be the case with AO-I, however.…”
Section: Reduction Of the Product Of Tnh2 Oxidation With Sodiummentioning
confidence: 87%
See 1 more Smart Citation
“…Amineoxidase from the epicotyl of Pisum sativum was purified and studied by MCGOWAN and MUIR (14). The purified enzyme has a molecular weight of 1.85 x 10 5 • The Km for tryptamine was 1.6 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Les diamines oxydases sont particulierement, actives chez les legumineuses telles que Pisum sativum, Vicia faba, Lens esculatum et Phaseolus vulgaris (Me Gowan et Muir, 1971 ;Yanagisawa et al, 1981 ;Federico et al, 1985;Suzuki et al, 1990). Les DAO oxydent les fonctions amines primaires des diamines, Put et Cad, mais peuvent aussi oxyder les fonctions primaires des polyamines, Spd et Spm (Smith, 1985).…”
Section: Metabolisme Des Polyaminesunclassified